Epoxy resin composition, cured product, semiconductor device, and method for manufacturing semiconductor device
Patent Information
- Application Number
- CN202580023546.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-01-29
- Publication Date
- 2026-11-03
AI Technical Summary
In semiconductor devices, as the interposer becomes larger, the stress on the seal increases, leading to defects such as cracks in the bump electrodes. Furthermore, the viscosity of existing underfill materials increases and the gap filling time becomes longer, affecting operability and reliability.
An epoxy resin composition containing specific core-shell rubber particles is used, specifically a combination of epoxy resin, curing agent, inorganic filler and core-shell rubber particles. The core-shell rubber particles are composed of (meth)acrylic acid and (meth)acrylate as structural units, with an average particle size of 0.03μm to 1.0μm, and are added at an amount of 1 to 30% by mass to reduce viscosity and improve injectability.
It achieves low viscosity, excellent injectability and high reliability, can effectively fill gaps, reduce the elastic modulus of the seal, reduce stress, and improve the accuracy and reliability of semiconductor devices.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to epoxy resin compositions, cured products, semiconductor devices, and methods for manufacturing semiconductor devices. Background Technology
[0002] Semiconductor devices are demanding higher performance, greater versatility, and lower power consumption. Currently, System-on-Chip (SoC) technology, which increases the transistor integration density of a single chip and provides full functionality, is the mainstream approach. However, this approach suffers from rising manufacturing costs and declining yield rates associated with larger chip sizes. To address this, System-in-Package (SiP) has emerged, which integrates multiple chips at high density. SiP incorporates a substrate with a silicon interposer. The silicon interposer is placed on the packaging substrate, and multiple chips are arranged laterally and close together on it. Furthermore, a multi-layer wiring circuit is formed on top of the silicon interposer, connecting to the underlying resin substrate via through-silicon vias (TSVs). Since active components such as transistors are not formed on the silicon interposer, its size is less complex compared to individual chips. Therefore, increasing the size of the silicon interposer and mounting more chips on it has become the mainstream approach. In addition, in order to further scale up, various interlayers, such as interlayers in which silicon is embedded in molding resin, are being studied.
[0003] The interlayer and the resin substrate are connected by bump electrodes. If thermal loads such as temperature cycling are applied, the difference in the linear thermal expansion coefficients of the components causes stress on the bump electrodes, leading to defects such as cracking. Therefore, a liquid sealing material called an underfill material is used to seal the gap between the interlayer and the resin substrate, thereby improving the resistance to thermal loads (thermal cycling resistance) and the property of protecting the encapsulation from heat and external forces (encapsulation protection) (Patent Document 1 and Patent Document 2). Furthermore, a method is known to reduce the elastic modulus of the cured product (sealing body) by adding a rubber component (e.g., core-shell rubber particles) to the underfill material (Patent Document 3). Existing technical documents Patent documents
[0004] Patent Document 1: Japanese Patent Application Publication No. 2017-171754 Patent Document 2: Japanese Patent Application Publication No. 2016-108358 Patent Document 3: Japanese Patent Application Publication No. 2019-81816 Summary of the Invention The technical problem that the invention aims to solve
[0005] In recent years, with the aim of increasing the performance and multifunctionality of semiconductor devices, the size of the interposer has been further developed. However, as the interposer becomes larger, the stress applied to the seal also increases. Therefore, there is a need for an underfill material that can mitigate the stress applied to the seal, suppress the occurrence of cracks in the seal, and simultaneously provide high bump protection.
[0006] Adding core-shell rubber particles to the underfill material can reduce the elastic modulus of the sealant. However, if the amount of rubber added increases, problems arise such as increased viscosity of the underfill material and decreased workability. Furthermore, the time required to fill the gap between the interlayer and the resin substrate (gap filling time) becomes longer. In this specification, the latter characteristic is described using the term "injectability." For example, a short gap filling time indicates excellent injectionability.
[0007] Therefore, the object of the present invention is to provide an epoxy resin composition containing core-shell rubber particles, wherein the epoxy resin composition has low viscosity and excellent injectability. Furthermore, the object of the present invention is to provide a cured product of the above-mentioned epoxy resin composition, a semiconductor device having the above-mentioned cured product, and a method for manufacturing the above-mentioned semiconductor device. Technical means to solve technical problems
[0008] In order to achieve the above-mentioned objectives, the inventors conducted in-depth research and discovered that the above-mentioned technical problems could be solved by using an epoxy resin composition containing specific core-shell rubber particles. This invention is based on these insights.
[0009] That is, the present invention provides an epoxy resin composition, wherein, The epoxy resin composition is an epoxy resin composition comprising epoxy resin (A), curing agent (B), inorganic filler (C), and core-shell rubber particles (D). As a core-shell rubber particle (D), it includes a core-shell rubber particle (D1) whose shell contains (meth)acrylic acid and (meth)acrylate as structural units.
[0010] Preferably, the shell layer in the core-shell rubber particle (D1) further contains at least one structural unit selected from the group consisting of methyl methacrylate and glycidyl methacrylate.
[0011] Preferably, the content of core-shell rubber particles (D1) relative to the total amount (100% by mass) of epoxy resin (A) and curing agent (B) is 1% to 30% by mass.
[0012] Preferably, the average particle size of the core-shell rubber particles (D1) is 0.03 μm to 1.0 μm.
[0013] Preferably, the content of inorganic filler (C) relative to the epoxy resin composition (100% by mass) is 50% by mass or more.
[0014] Preferably, the inorganic filler material (C) comprises silicon dioxide with an average particle size of less than 100 nm.
[0015] Preferably, the epoxy resin (A) comprises at least one selected from the group consisting of bisphenol type epoxy resin, aminophenol type epoxy resin and naphthalene type epoxy resin.
[0016] Preferably, the curing agent (B) is an amine-based curing agent.
[0017] Preferably, the shell of the core-shell rubber particle (D1) does not substantially contain styrene, acrylonitrile, and methacrylonitrile as structural units.
[0018] Preferably, the above-mentioned epoxy resin composition is used for semiconductor sealing.
[0019] The present invention also provides a cured product of the above-described epoxy resin composition.
[0020] This invention also provides a semiconductor device, wherein the semiconductor device comprises: substrate; Semiconductor elements disposed on the aforementioned substrate; and The cured material that seals the aforementioned semiconductor element.
[0021] The present invention also provides a method for manufacturing a semiconductor device, wherein the method for manufacturing the semiconductor device includes: The process of filling the gap between a substrate and a semiconductor element disposed on the substrate using the above-described epoxy resin composition; and The process of heating the above-mentioned epoxy resin composition to cure it. Beneficial effects
[0022] The epoxy resin composition of the present invention has low viscosity, thus exhibiting good workability. Furthermore, it has excellent injectability, enabling efficient filling of gaps in the epoxy resin composition even when manufacturing semiconductor devices using substrates such as large-scale interposers. Moreover, due to the aforementioned characteristics, it can contain a larger number of core-shell rubber particles compared to conventional epoxy resin compositions. Therefore, adjustments can be made to ensure that the cured epoxy resin composition exhibits a low elastic modulus. Consequently, semiconductor devices equipped with the cured epoxy resin composition can seal semiconductor elements with high precision using the cured composition, and exhibit high reliability due to the reduced stress applied to the cured epoxy resin composition. Attached Figure Description
[0023] Figure 1 Figures (a) to (c) illustrate “Evaluation 2: Gap Filling Test” in the embodiments. Detailed Implementation
[0024] (Epoxy resin composition) The epoxy resin composition described above comprises epoxy resin (A), curing agent (B), inorganic filler (C), and core-shell rubber particles (D). The core-shell rubber particles (D) comprise core-shell rubber particles (D1) whose shell contains (meth)acrylic acid and (meth)acrylate as structural units. The epoxy resin composition may further comprise the curing accelerator (E), coupling agent (F), and other components (G) described later. Furthermore, in this specification, "(meth)acrylic acid" is a concept encompassing both acrylic acid and methacrylic acid. Similarly, "(meth)acrylate" is a concept encompassing both acrylate and methacrylate.
[0025] ·Epoxy resin (A) The above-described epoxy resin composition, by containing epoxy resin (A), is capable of forming a cured product with high electrical insulation properties. The number of epoxy groups in epoxy resin (A) is not particularly limited, but is preferably two or more (i.e., a multifunctional epoxy resin). Epoxy resin (A) can be used alone or in combination of two or more types.
[0026] Epoxy resin (A) can be in liquid or solid form at room temperature (25°C), but liquid form is preferred from the viewpoint of the viscosity of the epoxy resin composition. Even solid epoxy resin is preferred when it exhibits a liquid state as a mixture by being used in combination with liquid epoxy resin.
[0027] The epoxy resin (A) is not particularly limited, and examples thereof include bisphenol-type epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin and bisphenol AF epoxy resin, biphenol-type epoxy resin, cyclohexane-type epoxy resin, dicyclopentadiene-type epoxy resin, trisphenol-type epoxy resin, naphthol novolac-type epoxy resin, phenol novolac-type epoxy resin, tert-butyl-catechol-type epoxy resin, naphthalene-type epoxy resin, naphthol-type epoxy resin, anthracene-type epoxy resin, glycidylamine-type epoxy resin (glycidylamine-type epoxy resin having no aromatic structure or glycidylamine-type epoxy resin having an aromatic structure), glycidyl ester-type epoxy resin (glycidyl ester-type epoxy resin having no aromatic structure or glycidyl ester-type epoxy resin having an aromatic structure), cresol novolac-type epoxy resin, biphenyl-type epoxy resin, linear aliphatic epoxy resin (linear aliphatic epoxy resin having no aromatic structure or linear aliphatic epoxy resin having an aromatic structure), epoxy resin having a butadiene structure (epoxy resin having a butadiene structure and no aromatic structure or epoxy resin having a butadiene structure and an aromatic structure), alicyclic epoxy resin (alicyclic epoxy resin having no aromatic structure or alicyclic epoxy resin having an aromatic structure, heterocyclic epoxy resin, spiro ring-containing epoxy resin (spiro ring-containing epoxy resin having no aromatic structure or spiro ring-containing epoxy resin having an aromatic structure), cyclohexanedimethanol-type epoxy resin (cyclohexanedimethanol-type epoxy resin having no aromatic structure or cyclohexanedimethanol-type epoxy resin having an aromatic structure), naphthylene ether-type epoxy resin, trimethylol-type epoxy resin (trimethylol-type epoxy resin having no aromatic structure or trimethylol-type epoxy resin having an aromatic structure), tetraphenylmethane-type epoxy resin, aminophenol-type epoxy resin, and aromatic or aliphatic epoxy resins such as silicone-modified epoxy resin.
[0028] Among these, the epoxy resin (A) preferably contains at least one selected from the group consisting of bisphenol-type epoxy resins, naphthalene-type epoxy resins, aminophenol-type epoxy resins, cyclohexane-type epoxy resins and glycidylamine-type epoxy resins, more preferably contains at least one selected from the group consisting of bisphenol F epoxy resins, naphthalene-type epoxy resins, aminophenol-type epoxy resins and cyclohexane-type epoxy resins (particularly 1,4-diglycidylcyclohexane), and further preferably contains at least one selected from the group consisting of bisphenol-type epoxy resins, aminophenol-type epoxy resins and naphthalene-type epoxy resins.
[0029] The content of bisphenol-type epoxy resin relative to epoxy resin (A) (100% by mass) is not particularly limited, but is preferably 0% to 100% by mass. The content of naphthalene-type epoxy resin relative to epoxy resin (A) (100% by mass) is not particularly limited, but is preferably 0% to 50% by mass. The content of aminophenol-type epoxy resin relative to epoxy resin (A) (100% by mass) is not particularly limited, but is preferably 0% to 90% by mass. The content of cyclohexane-type epoxy resin relative to epoxy resin (A) (100% by mass) is not particularly limited, but is preferably 0% to 30% by mass.
[0030] Specific examples of liquid epoxy resins include "YDF-8170" (bisphenol F type epoxy resin), "YDF-8125" (bisphenol A type epoxy resin), "ZX-1658" and "ZX-1658GS" (liquid 1,4-glycidylcyclohexane) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "HP-4032", "HP-4032D" and "HP-4032SS" (naphthalene type epoxy resin) manufactured by DIC Corporation; and epoxy resins manufactured by Mitsubishi Chemical Co., Ltd. The following epoxy resins are listed: "jER828US", "jER828EL" (bisphenol A type epoxy resin), "jER806", "jER807" (bisphenol F type epoxy resin), "jER152" (phenolic varnish type epoxy resin), "jER630", "jER630LSD", "EP3980S" (aminophenol type epoxy resin), and "YX7400" (high resilience epoxy resin); "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; Nagase. ChemteX Co., Ltd. manufactures "EX-721" (glycidyl ester type epoxy resin); and Daicel Co., Ltd. manufactures "CELLOXIDE 2021P" (alicyclic epoxy resin).
[0031] Specific examples of solid epoxy resins include "HP-4032H" (naphthalene-type epoxy resin), "HP-4700", "HP-4710" (naphthalene-type tetrafunctional epoxy resin), "N-690" (cresol phenolic varnish type epoxy resin), "N-695" (cresol phenolic varnish type epoxy resin), "HP-7200", "HP-7200L", "HP-7200HH", "HP-7200H", "HP-7200HHH" (dicyclopentadiene type epoxy resin), "EXA7311", and "EXA7" manufactured by DIC Corporation. 311-G3, EXA7311-G4, EXA7311-G4S, HP6000 (naphthyl ether type epoxy resin); EPPN-502H (triphenol type epoxy resin), NC-7000-L (naphthol phenolic varnish type epoxy resin), NC-3000-H, NC-3000, NC-3000-L, NC-3100 (biphenyl type epoxy resin) manufactured by Nippon Chemical Materials Co., Ltd.; ESN475V (naphthol type epoxy resin), ES... N485 (naphthol phenolic varnish type epoxy resin); "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bixylenol type epoxy resin), "YL7760" (bisphenol AF type epoxy resin), "YX8800" (anthracite type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" manufactured by Mitsubishi Chemical Corporation. (Solid bisphenol A type epoxy resin), "jER1031S" (tetraphenylethane type epoxy resin), "jER157S70" (bisphenol phenolic varnish type epoxy resin); "YX4000HK" (bi-xylenol type epoxy resin), "YX8800" (anthracite type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation.
[0032] The epoxy equivalent of epoxy resin (A) is not particularly limited, but is preferably 30 g / eq to 1000 g / eq, more preferably 40 g / eq to 500 g / eq, and even more preferably 50 g / eq to 300 g / eq.
[0033] The content of epoxy resin (A) relative to the above-described epoxy resin composition (100% by mass) is not particularly limited, but is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, and particularly preferably 12% by mass or more. Furthermore, it is preferably 60% by mass or less, more preferably 50% by mass or less, further preferably 45% by mass or less, and particularly preferably 40% by mass or less. By keeping the content of epoxy resin (A) within the above-described range, there is a tendency for the thermal expansion of the cured product to decrease and the toughness to increase. Furthermore, there is a tendency for the epoxy resin composition to have low viscosity and excellent injection properties.
[0034] • Curing agent (B) The curing agent (B) is not particularly limited to any curing agent that initiates, proceeds, or promotes the polymerization of the epoxy resin; examples include amine-based curing agents, acid anhydride-based curing agents, and phenol-based curing agents. The curing agent (B) can be solid or liquid at room temperature (25°C), preferably liquid. One type of curing agent (B) can be used alone, or two or more can be used in combination.
[0035] Examples of aromatic amines that can be used as the aforementioned amine-based curing agents include 4,4'-methylenebis(2-ethylaniline), ethyltoluenediamine, diethyltoluenediamine (such as 3,5-diethyltoluene-2,4-diamine and 3,5-diethyltoluene-2,6-diamine), 1-methyl-3,5-diethyl-2,4-diaminobenzene, 1-methyl-3,5-diethyl-2,6-diaminobenzene, 1,3,5-triethyl-2,6-diaminobenzene, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,5,3',5'-tetramethyl-4,4'-diaminodiphenylmethane, and dimethylthiotoluenediamine. Examples of anhydride-based curing agents include alkylated tetrahydrophthalic anhydride such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, phthalic anhydride, dodecenylsuccinic anhydride, and methylnadic anhydride. Examples of phenolic curing agents include phenolic varnish resin, cresol varnish resin, naphthol-modified phenolic resin, dicyclopentadiene-modified phenolic resin, and p-xylene-modified phenolic resin. Examples of imidazole-based curing agents include 2-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-imidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Furthermore, microencapsulated imidazole-based curing agents can also be cited as examples of imidazole-based curing agents. From the viewpoints of temperature cycling resistance, moisture resistance, and reliability of semiconductor devices, the curing agent (B) is preferably the above-mentioned amine-based curing agent, more preferably an aromatic amine, and even more preferably a liquid aromatic amine.
[0036] The equivalent amount (molecular weight of each functional group) of the curing agent (B) is not particularly limited, but is preferably 10 g / eq to 300 g / eq, more preferably 20 g / eq to 160 g / eq, and even more preferably 30 g / eq to 100 g / eq.
[0037] The content of curing agent (B) is not particularly limited, but it is preferred to be an amount in which the stoichiometric equivalent ratio (curing agent equivalent / epoxy group equivalent) with epoxy resin (A) is 0.5 to 1.5, and more preferably an amount in which the equivalent ratio is 0.8 to 1.2.
[0038] The content of curing agent (B) relative to the epoxy resin composition (100% by mass) of the present invention is not particularly limited, but is preferably 2% by mass or more, more preferably 4% by mass or more, and even more preferably 5% by mass or more. Furthermore, it is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, and particularly preferably 12% by mass or less. By keeping the content of curing agent (B) within the above-mentioned range, there is a tendency for the thermal expansion of the cured product to decrease and the toughness to increase. Furthermore, there is a tendency for the epoxy resin composition to have low viscosity and excellent injection properties.
[0039] Inorganic filler materials (C) The inorganic filler material (C) is not particularly limited, but is preferably: (1) an inorganic filler material having the property of suppressing volume shrinkage (curing shrinkage) caused by the curing reaction of the epoxy resin composition; (2) an inorganic filler material having the property of suppressing volume change (thermal shrinkage) caused by heating of the cured material, that is, an inorganic filler material having the effect of reducing the coefficient of linear expansion by adding it; or (3) an inorganic filler material having both of these properties.
[0040] Examples of inorganic filler materials (C) include silicon dioxide, silicon carbide, silicon nitride, aluminum oxide, aluminum nitride, aluminum hydroxide, aluminum silicate, magnesium silicate, calcium silicate, calcium carbonate, barium sulfate, barium carbonate, titanium oxide, calcium sulfate, potassium titanate, magnesium carbonate, zinc oxide, boron nitride, zirconium oxide, and their surface-treated inorganic particles. From the viewpoint of increasing the filler content, silicon dioxide is preferred, and silicon dioxide with an average particle size of 100 nm or less is more preferred (also referred to as "nano-silica"). Furthermore, from the viewpoint of improving thermal conductivity, aluminum oxide is preferred. One type of inorganic filler material (C) can be used alone, or two or more types can be used in combination.
[0041] From the viewpoint of achieving an appropriate range of viscosity in the epoxy resin composition, the inorganic filler material (C) is preferably an inorganic filler material that has undergone surface treatment using a coupling agent having functional groups such as epoxy groups, (meth)acryloyl groups, or amino groups (especially phenylamino groups). Examples of such coupling agents include silane coupling agents such as 3-epoxypropoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane. The surface treatment of the inorganic filler material (C) can be performed using one of the aforementioned coupling agents alone, or in combination of two or more.
[0042] The shape of the inorganic filler material (C) is not particularly limited, and examples include spherical (true sphere, approximately true sphere, etc.), polyhedral, rod-shaped (cylindrical, prismatic, etc.), flat, scaly, and irregular shapes. Among these, spherical shape is preferred from the viewpoint of achieving a high filling volume.
[0043] The average particle size of the inorganic filler (C) is not particularly limited, but is preferably 1 nm to 10 μm, more preferably 0.1 μm to 8 μm, and more preferably 0.3 μm to 5 μm. By making the average particle size of the inorganic filler (C) within the above range, the viscosity of the epoxy resin composition becomes suitable, and the decrease in the filling rate into the gaps becomes less likely to occur. In addition, for the purpose of adjusting the viscosity of the epoxy resin composition, two or more fillers with different average particle sizes may be used together. In this specification, the method for measuring the average particle size of the inorganic filler (C) is not particularly limited, and for example, a laser diffraction and scattering particle size distribution measuring device (product name: LS 13 320, manufactured by Beckman Coulter) can be used for measurement.
[0044] The content of inorganic filler (C) relative to the above-mentioned epoxy resin composition (100% by mass) is not particularly limited, but is preferably 20% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and particularly preferably 50% by mass or more. Furthermore, it is preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less. By keeping the content of inorganic filler (C) within the above-mentioned range, there is a tendency to reduce the coefficient of thermal expansion of the epoxy resin composition while maintaining good workability such as low viscosity and excellent injectability. When nano-silica is included, its content is not particularly limited, but is, for example, 0.1% by mass to 30% by mass relative to inorganic filler (C) (100% by mass), more preferably 0.1% by mass to 20% by mass, further preferably 0.1% by mass to 10% by mass, and particularly preferably 0.3% by mass to 5% by mass.
[0045] Core-shell rubber particles (D) The core-shell rubber particles (D) have the effect of suppressing the occurrence and propagation of filler cracks when epoxy resin compositions are used as underfill materials. Specifically, the combination of core-shell rubber particles (D) results in a low elastic modulus of the cured epoxy resin composition, which in turn reduces the stress generated at the filler corners, thus suppressing the occurrence of filler cracks. Furthermore, in the event of existing filler cracks, the core-shell rubber particles (D) act as a stress reliever, inhibiting the propagation of the filler cracks.
[0046] Core-shell rubber particles (D) refer to rubber particles consisting of a core and one or more shells covering the core. Core-shell rubber particles (D) have a core made of a material with excellent flexibility and a shell made of a material with excellent affinity for the components contained in the epoxy resin composition (especially epoxy resin (A)), thereby achieving a low elastic modulus of the cured product while exhibiting good dispersibility in the epoxy resin composition.
[0047] In core-shell rubber particles (D), materials constituting the core include, for example, silicone rubbers such as polydimethylsiloxane, butadiene rubbers, styrene rubbers, acrylic rubbers, polyolefin rubbers, and silicone / acrylic composite rubbers.
[0048] As materials constituting the shell, monomers with epoxy groups and monomers without epoxy groups can be cited as examples. That is, the shell contains monomers with epoxy groups and / or monomers without epoxy groups as structural units.
[0049] Examples of monomers containing epoxy groups include glycidyl acrylate, glycidyl methacrylate, 4-hydroxybutyl glycidyl acrylate ether, and other glycidyl acrylates containing glycidyl groups; and vinyl monomers containing glycidyl groups such as allyl glycidyl ether.
[0050] Examples of monomers lacking epoxy groups include unsaturated carboxylic acids, (meth)acrylates lacking epoxy groups, aromatic vinyl compounds, and vinyl cyanide compounds. Examples of unsaturated carboxylic acids include (meth)acrylic acid, itaconic acid, crotonic acid, and maleic anhydride. Examples of (meth)acrylates lacking epoxy groups include methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate. 1-5 Alkyl esters. Examples of the above-mentioned aromatic vinyl compounds include vinylbenzenes such as styrene, α-methylstyrene, p-methylstyrene, and divinylbenzene. Examples of the above-mentioned vinyl cyanide compounds include acrylonitriles and methacrylonitrs.
[0051] As core-shell rubber particles (D), the epoxy resin composition of the present invention comprises core-shell rubber particles (D1) whose shell contains (meth)acrylic acid and (meth)acrylate as structural units. Furthermore, the above-mentioned epoxy resin composition may also comprise core-shell rubber particles (D2) other than core-shell rubber particles (D1). One type of core-shell rubber particle (D) may be used alone, or two or more types may be used in combination.
[0052] By including core-shell rubber particles (D1) in the above-mentioned epoxy resin composition, the viscosity of the epoxy resin composition can be adjusted to be low, thus improving workability. Furthermore, the injectability of the epoxy resin composition is improved, allowing for efficient filling of gaps. Moreover, due to the aforementioned properties of the core-shell rubber particles (D1), a larger quantity can be added to the epoxy resin composition compared to conventional core-shell rubber particles. Therefore, adjustments can be made to allow the cured epoxy resin composition to exhibit a lower modulus of elasticity.
[0053] The core-shell rubber particles (D1) may further contain methyl methacrylate and glycidyl methacrylate (e.g., glycidyl methacrylate) as structural units in the shell. On the other hand, it is preferable that they do not contain styrene, acrylonitrile, and methacrylonitrile as structural units. By adopting the above structure in the core-shell rubber particles (D1), there is a tendency for the epoxy resin composition to have low viscosity and excellent injection properties.
[0054] The average particle size of the core-shell rubber particles (D) (preferably core-shell rubber particles (D1)) is not particularly limited, but is preferably 0.03 μm to 1.0 μm, more preferably 0.04 μm to 0.8 μm, and even more preferably 0.05 μm to 0.7 μm. Furthermore, as a method for determining the average particle size of the core-shell rubber particles (D), one example is to observe the cross-section of the cured product obtained by curing the above-mentioned epoxy resin composition using a scanning electron microscope (SEM). Specifically, SEM can be used to measure any particle size of 100 μm. 2 Observe within a certain range. For the confirmed core-shell rubber particles (D) or the diameter of the concave part after the core-shell rubber particles (D) fall off, randomly select 10 locations and take their average value as the average particle size of the core-shell rubber particles (D).
[0055] The content of core-shell rubber particles (D) relative to the above-described epoxy resin composition (100% by mass) is not particularly limited, but is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, particularly preferably 15% by mass or less, and most preferably 10% by mass or less. Furthermore, it is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, and particularly preferably 1.5% by mass or more.
[0056] The content of core-shell rubber particles (D1) relative to the above-described epoxy resin composition (100% by mass) is not particularly limited, but is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, particularly preferably 15% by mass or less, and most preferably 10% by mass or less. Furthermore, it is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, and particularly preferably 1.5% by mass or more. By keeping the content of core-shell rubber particles (D1) within the above-described range, there is a tendency for the epoxy resin composition to have low viscosity and excellent injectability.
[0057] The content of core-shell rubber particles (D) relative to the total amount (100% by mass) of epoxy resin (A) and curing agent (B) is not particularly limited, but is preferably 1% to 60% by mass, more preferably 1% to 45% by mass, and even more preferably 1% to 30% by mass.
[0058] The content of core-shell rubber particles (D1) relative to the total amount (100% by mass) of epoxy resin (A) and curing agent (B) is not particularly limited, but is preferably 1% to 60% by mass, more preferably 1% to 45% by mass, and even more preferably 1% to 30% by mass. By keeping the content of core-shell rubber particles (D1) within the above range, there is a tendency for the epoxy resin composition to have low viscosity and excellent injection properties.
[0059] Core-shell rubber particles (D) can be manufactured using known or conventional methods, such as through the core formation process and shell formation process described below. • Core forming process: The process of forming the material that forms the core. For example, it includes: forming polysiloxane by emulsification polymerization; and forming acrylic rubber by polymerizing monomers containing alkyl methacrylates in the presence of an emulsifier and an initiator. • Shell formation process: A process in which monomers having epoxy groups and / or monomers without epoxy groups are added to a system containing the nuclei obtained in the core formation process, and an initiator is added as needed, and the monomers are copolymerized in the presence of the nuclei to form a shell.
[0060] • Curing accelerator (E) Curing accelerators (E) have the property of promoting the curing of epoxy resins. There are no particular limitations on curing accelerators; examples include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Commercially available products include 2-phenyl-4-methylimidazole (manufactured by Shikoku Kasei Corporation, product name "2P4MZ"), 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine (manufactured by Shikoku Kasei Corporation, product name "2MZA"), and dicyandiamide. Furthermore, encapsulated imidazoles, also known as microencapsulated imidazoles or epoxy adduct imidazoles, can also be used. Examples include "HX3941HP", "HXA3942HP", "HXA3922HP", "HXA3792", "HX3748", "HX3721", "HX3722", "HX3088", "HX3741", "HX3742", and "HX3613" (all manufactured by Asahi Kasei Chemicals Co., Ltd.); "PN-23J", "PN-40J", and "PN-50" (manufactured by Ajinomoto Precision Technology Co., Ltd.); and "FXR-1121" (manufactured by Fuji Chemical Industries Co., Ltd.). Curing accelerators (E) can be used alone or in combination of two or more.
[0061] The content of the curing accelerator (E) relative to the above-described epoxy resin composition (100% by mass) is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.02% by mass or more. Furthermore, it is not particularly limited, but is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, even more preferably 1.0% by mass or less, and particularly preferably 0.5% by mass or less.
[0062] • Coupling agent (F) There are no particular limitations on the coupling agent (F). Examples include silane coupling agents such as vinyl-based, epoxy-propoxy-based, methacrylic-based, amino-based, mercapto-based, or imidazole-based agents; titanium coupling agents such as alkoxide-based, chelate-based, or acylate-based agents; and long-chain spacer-type coupling agents such as epoxy-propoxy-octyltrimethoxysilane or methacryl-octyltrimethoxysilane. One coupling agent (F) can be used alone, or two or more can be used in combination.
[0063] Examples of silane coupling agents include 3-epoxypropoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane.
[0064] The content of coupling agent (F) relative to the above-described epoxy resin composition (100% by mass) is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. Furthermore, its content is not particularly limited, but is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and even more preferably 1.0% by mass or less.
[0065] Other ingredients (G) The epoxy resin composition described above may also contain components other than epoxy resin (A), curing agent (B), inorganic filler (C), core-shell rubber particles (D), curing accelerator (E), and coupling agent (F) (hereinafter referred to as "other components (G)"). Examples of other components (G) include: curable compounds other than epoxy resin (A), thermoplastic resins such as acrylic resin, polyethylene resin, polyester resin, polyurethane resin, and polyamide resin, ion traps, surfactants, antioxidants, defoamers, flame retardants, colorants, reactive diluents, solvents, etc. Other components (G) may be used alone or in combination of two or more.
[0066] The content of other components (G) relative to the above-described epoxy resin composition (100% by mass) is not particularly limited as long as it does not impair the effects of the present invention. For example, it is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. Furthermore, it is not particularly limited, for example, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more.
[0067] (Physical properties and manufacturing method of epoxy resin composition) The viscosity of the above-mentioned epoxy resin composition at 25°C is not particularly limited, but is preferably 0.1 Pa·s to 100 Pa·s, more preferably 1 Pa·s to 60 Pa·s, even more preferably 3 Pa·s to 50 Pa·s, and particularly preferably 5 Pa·s to 40 Pa·s. By keeping the viscosity within the above range, it tends to be easier to fill the gaps. In addition, the above viscosity can be measured as described in the following examples using a Brookfield viscometer (model: HBDV-1 Brookfield) at a liquid temperature of 25°C and rotating at 50 rpm for 1 minute.
[0068] The epoxy resin composition described above can be prepared by known and conventional methods. For example, epoxy resin (A), curing agent (B), inorganic filler (C), and core-shell rubber particles (D), and at least one component selected from the group consisting of curing accelerator (E), coupling agent (F), and other components (G) as needed, can be introduced into a suitable mixer, heated as needed to melt and stir and mix simultaneously, thereby obtaining the epoxy resin composition described above. When the epoxy resin (A) is solid, it is preferable to mix it by heating to liquefy or fluidize it. If it is difficult to uniformly disperse the inorganic filler (C) in the epoxy resin composition, the epoxy resin (A) and inorganic filler (C) can be heated and mixed to uniformly disperse the inorganic filler (C) in the epoxy resin (A), then cooled as needed, and components such as curing agent (B) are further mixed to prepare the epoxy resin composition described above.
[0069] The aforementioned mixer is not particularly limited, and examples include roller mills, pulverizers, Henschel mixers, drum mixers, self-rotating mixers, and planetary mixers equipped with stirring and heating devices. The mixing ratio of each component is appropriately set according to the content ratio of each component in the epoxy resin composition.
[0070] The epoxy resin composition described above is preferably used as a material for sealing semiconductor elements, wiring, solder (solder bumps), and other materials disposed on a substrate in a semiconductor device (epoxy resin composition for semiconductor sealing). By using the epoxy resin composition described above as an epoxy resin composition for semiconductor sealing, a highly reliable semiconductor device can be manufactured. Furthermore, the epoxy resin composition described above can preferably be used as a material for sealing semiconductor elements disposed on a substrate in a flip-chip semiconductor device (epoxy resin composition for flip-chip semiconductor sealing). Specifically, by filling the gap between the semiconductor element and the substrate with the epoxy resin composition and performing thermosetting, the bump electrodes present in the gap are sealed, and the semiconductor element and the substrate are fixed together as a sealing body, thereby improving reliability.
[0071] The epoxy resin composition described above for semiconductor sealing can be used, for example, as a capillary underfill material, a liquid molding underfill material, a secondary underfill material, a pre-supply type underfill material, a top encapsulation material, and a liquid compression molding material. The epoxy resin composition described above is not limited to its use as an epoxy resin composition for semiconductor sealing; for example, it can be used as an adhesive for fixing, joining, or protecting components constituting electronic parts.
[0072] (Cure of epoxy resin composition) A cured product is formed by curing the above-described epoxy resin composition. The curing method is not particularly limited; for example, it can be performed by heat treatment of the epoxy resin composition. The heat treatment temperature is not particularly limited; for example, 60°C to 200°C is preferred, and 80°C to 180°C is more preferred. The heat treatment time is not particularly limited; for example, 0.1 hours to 5 hours is preferred, and 0.5 hours to 3 hours is more preferred.
[0073] (Semiconductor devices) The semiconductor device of the present invention includes a substrate, a semiconductor element disposed on the substrate, and a cured epoxy resin composition sealing the semiconductor element. The semiconductor device is preferably a flip-chip type semiconductor device. The flip-chip type semiconductor device has a structure in which an electrode portion on the substrate is connected to the semiconductor element by means of bump electrodes. Furthermore, in the semiconductor device, the gap between the semiconductor element and the substrate is sealed by the cured epoxy resin composition (sealing agent).
[0074] By filling the gap between the substrate and the semiconductor element disposed on the substrate using the aforementioned epoxy resin composition (filling process), and then heating the epoxy resin composition to cure it (sealing process), a semiconductor device can be manufactured. The method for filling the gap with the epoxy resin composition is not particularly limited; for example, while heating the substrate to 50°C to 120°C, the epoxy resin composition is applied to one end of the substrate or the semiconductor element, and the epoxy resin composition fills the gap between the substrate and the semiconductor element through capillary action. After filling the gap with the epoxy resin composition, the gap is sealed by heating the substrate at a predetermined temperature for a predetermined time (specifically, the temperature and time described in the heat treatment for forming the cured product). Example
[0075] The present invention will now be described in more detail based on embodiments, but the present invention is not limited to the embodiments.
[0076] The epoxy resin compositions of Examples 1 to 6 and Comparative Example 1 were prepared by appropriately selecting and mixing epoxy resin (A), curing agent (B), inorganic filler (C), and core-shell rubber particles (D), and at least one component selected as needed from the group consisting of curing accelerator (E), coupling agent (F), and other components (G) to achieve the formulations shown in Table 1. The numerical values related to each component in Table 1 represent parts by mass.
[0077] The following is a description of each component in Table 1. ·Epoxy resin (A) YDF-8170 (Product Name): Bisphenol F type epoxy resin, epoxy equivalent 160g / eq, liquid at 25℃, manufactured by Nippon Steel Chemical Materials Co., Ltd. HP-4032D (Product Name): Naphthalene-type epoxy resin, epoxy equivalent 140g / eq, liquid at 25℃, manufactured by DIC Corporation. JER630 (Product Name): Aminophenol type epoxy resin, epoxy equivalent 98 g / eq, liquid at 25°C, manufactured by Mitsubishi Chemical Corporation. ZX-1658GS (Product Name): 1,4-glycidylcyclohexane, epoxy equivalent 135g / eq, liquid at 25°C, manufactured by Nippon Steel Chemical Materials Co., Ltd. • Curing agent (B) HD AA: Product name / KAYAHARD AA, 4,4'-methylenebis(2-ethylaniline), active hydrogen equivalent of 63g / eq, manufactured by Nippon Kayaku Co., Ltd. EH-105L (Product Name): Modified Aromatic Amine Curing Agent, Active Hydrogen Equivalent: 61g / eq, Manufactured by ADEKA Co., Ltd. ETHACURE 100plus (Product Name): Diethyltoluene diamine, manufactured by Albemarle Co., Ltd. Inorganic filler materials (C) YA010A-JGP (Product Name): Masterbatch of nano-silica with an average particle size of 10nm and bisphenol F type epoxy resin (mass ratio of the former:the latter = 25:75), nano-silica with surface treatment of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, manufactured by Adoma Technology Co., Ltd. The values in Table 1 are the mass of nano-silica; the mass fraction of bisphenol F type epoxy resin is added to YDF-8170. SE5050-SEJ (Product Name): Silica with an average particle size of 1.5μm, surface-treated with 3-epoxypropoxypropyltrimethoxysilane, manufactured by Adoma Technology Co., Ltd. Core-shell rubber particles (D) Rubber Particle 1: Core-shell rubber particle (equivalent to core-shell rubber particle (D1)), average particle size: 0.3 μm, core / silicone-based rubber (polydimethylsiloxane), shell / containing methacrylic acid, butyl acrylate, methyl methacrylate and glycidyl methacrylate as structural units. Rubber Particle 2: Core-shell rubber particle (equivalent to core-shell rubber particle (D2)), average particle size: 0.3 μm, core / silicone-based rubber (polydimethylsiloxane), shell / containing methyl methacrylate, glycidyl methacrylate, styrene and acrylonitrile as structural units. • Curing accelerator (E) CG-1400 / Product name "AMICURE CG-1400": Dicyandiamide, manufactured by Evonik Japan Co., Ltd. • Coupling agent (F) KBM-403 (Product Name): 3-Epoxypropoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Industry Co., Ltd. Other ingredients (G) CB: Special Black 4 powder (product name), carbon black, manufactured by Orion Engineered Carbon Co., Ltd. TPP (product name): Triphenylphosphine, a thickening inhibitor, manufactured by Hokho Chemical Co., Ltd. Irganox 1010 (Product Name): Pentaerythritol tetra[3-[3,5-di(tert-butyl)-4-hydroxyphenyl]propionate], antioxidant, manufactured by BASF Japan Co., Ltd. KF-6013: Polyether-modified silicone, surfactant, manufactured by Shin-Etsu Chemical Industry Co., Ltd.
[0078] (Evaluation 1: Viscosity determination at 25℃) The viscosity (Pa·s) of the epoxy resin compositions of Examples 1 to 6 and Comparative Example 1 at 25°C was measured using a Brookfield viscometer (model: HBDV-1, manufactured by Brookfield) at a liquid temperature of 25°C and a rotation speed of 50 rpm for 1 minute. The results are recorded in the "Viscosity at 25°C" section of Table 1.
[0079] (Evaluation 2: Gap Filling Test) • Production of experimental films The strip is inserted to make the gap between the two glass slides 50 μm, and the glass slides are offset by 1 cm and fixed to ensure the coating of the evaluation sample, thereby obtaining the test piece.
[0080] • Testing and evaluation The test piece was placed on a hot plate set to 110°C. Approximately 1g of the epoxy resin compositions of Examples 1 to 6 and Comparative Example 1 were applied to the coated portion of the sample, and the time it took for the filling distance to reach 20mm was measured.
[0081] use Figure 1 The gap filling test is explained. Figure 1In the diagram, 1 represents the test piece. 2 and 2' are glass slides. 3 is a band. 4 is a gap. 5 is the evaluation sample. (a) is a top view of test piece 1, with the long side of test piece 1 as the longitudinal direction and the short side as the transverse direction. (b) is a side view viewed from the long side direction of test piece 1. (c) is a side view viewed from the short side direction of test piece 1. Glass slide 2 is stacked with another glass slide 2' across band 3. As shown in (b), glass slides 2 and 2' are stacked with a 1 cm misalignment along their long sides. This misalignment is the coating area (sample coating area) of evaluation sample 5. Gap 4 is the space formed by using glass slide 2 for its top surface, glass slide 2' for its bottom surface, and two bands 3 for its sides. In gap 4, the distance between glass slides 2 and 2' is 50 μm, and the distance between the two bands 3 is 10 mm. The distance along the long side of gap 4 is 70 mm. Test piece 1 was placed on a hot plate (not shown), and evaluation sample 5 was coated onto the sample coating area. The coated evaluation sample 5 moved downwards along gap 4 (a) via capillary action. The time it took for evaluation sample 5 to reach the end of slide 2' was measured and recorded in Table 1, under "Gap Filling Time". The unit is seconds (s). A shorter gap filling time indicates better injection performance.
[0082] (Evaluation 3: Elastic modulus) • Production of experimental films An epoxy resin composition of Example 1 and Comparative Example 1 was applied to a glass plate (120mm × 120mm, the silicone resin release agent being a silicone resin release agent obtained by mixing toluene and KS841 (manufactured by Shin-Etsu Chemical Industry Co., Ltd.) at a mass ratio of 5:1, and further mixing with CAT-PL-50T (curing agent, manufactured by Shin-Etsu Chemical Industry Co., Ltd.) treated with a silicone resin release agent to make it 50mm × 10mm or larger, thereby forming a coating film. Then, another glass plate as described above was prepared, and the coated epoxy resin composition was sandwiched between it. At this time, a 2.0mm copper plate was sandwiched as a spacer, and the glass plate was fixed with a 25mm wide long-tail clip. It was placed at 165°C for 2 hours to cure the coating film. The cured coating film was peeled off from the glass plate and cut to a predetermined size (50mm × 10mm × 2.0mm) using a precision cutter to obtain a test piece.
[0083] • Testing and evaluation The storage modulus of elasticity (GPa) of the above test pieces was measured using the DCB method with a DMA7100 manufactured by Hitachi High Technology Sciences. The frequency was set to 1 Hz, and the heating rate was set to 3 °C / min. The storage modulus of elasticity (GPa) at 30 °C is recorded in the "Modulus of Elasticity (GPa)" section of the evaluation results in Table 2.
[0084] Table 1
[0085] Table 2
[0086] The following assessments can be conducted based on the evaluation results. (1) From the viewpoint of viscosity and injectability of epoxy resin compositions, it is preferable that the shell of the core-shell rubber particles contains butyl methacrylate as a structural unit. This is believed to be because, compared to the case containing methyl methacrylate or ethyl methacrylate as structural units, the side chain (acrylic group) has more carbon atoms, thus improving the wettability of the core-shell rubber particles with epoxy resin (A). The reason for the improved wettability is not yet clear, but the following reasons can be considered: (a) The side chain of the shell is long, making the shell more hydrophobic and improving the compatibility with epoxy resin; (b) Even assuming that a portion of the core is not covered by the shell (referred to as the "exposed portion"), the long side chain of the shell allows the side chain to cover the exposed portion, thus, similar to (a), the core-shell rubber particles can exhibit high compatibility with epoxy resin. (2) From the viewpoint of compatibility with epoxy resin (A), the shell of the core-shell rubber particles preferably does not contain aromatic vinyl compounds such as styrene or vinyl cyanide compounds such as acrylonitrile as structural units. In particular, the molecular skeleton of aromatic vinyl compounds is large, so steric hindrance can be considered to lead to a deterioration of liquid properties (e.g., increased viscosity).
[0087] Furthermore, it can be said that the low viscosity of the epoxy resin composition is correlated to some extent with its excellent injectability. However, injectability is affected not only by the viscosity of the epoxy resin composition, but also by factors such as contact angle, surface tension, and reactivity. Therefore, a decrease in viscosity does not necessarily correlate with an increase in injectability. From this perspective, it can be said that the epoxy resin composition of the present invention achieves an effective effect in possessing both low viscosity and excellent injectability.
[0088] In summary, the composition and variations of this disclosure are noted below. [1] An epoxy resin composition, wherein... The epoxy resin composition is an epoxy resin composition comprising epoxy resin (A), curing agent (B), inorganic filler (C), and core-shell rubber particles (D). As a core-shell rubber particle (D), it includes a core-shell rubber particle (D1) whose shell contains (meth)acrylic acid and (meth)acrylate as structural units. [2] The epoxy resin composition according to [1], wherein the epoxy resin (A) comprises at least one selected from the group consisting of bisphenol type epoxy resin, naphthalene type epoxy resin, aminophenol type epoxy resin, cyclohexane type epoxy resin and glycidylamine type epoxy resin, or comprises at least one selected from the group consisting of bisphenol F type epoxy resin, naphthalene type epoxy resin, aminophenol type epoxy resin and cyclohexane type epoxy resin (especially 1,4-glycidylcyclohexane), or comprises at least one selected from the group consisting of bisphenol type epoxy resin, aminophenol type epoxy resin and naphthalene type epoxy resin. [3] According to the epoxy resin composition of [1] or [2], wherein the content of bisphenol type epoxy resin relative to epoxy resin (A) (100% by mass) is 0% by mass to 100% by mass. [4] The epoxy resin composition according to any one of [1] to [3], wherein the content of naphthalene-type epoxy resin relative to epoxy resin (A) (100% by mass) is 0% to 50% by mass. [5] The epoxy resin composition according to any one of [1] to [4], wherein the content of the aminophenol type epoxy resin relative to epoxy resin (A) (100% by mass) is 0% to 90% by mass. [6] The epoxy resin composition according to any one of [1] to [5], wherein the content of cyclohexane-type epoxy resin relative to epoxy resin (A) (100% by mass) is 0% to 30% by mass. [7] The epoxy resin composition according to any one of [1] to [6], wherein the epoxy equivalent of the epoxy resin (A) is 30 g / eq to 1000 g / eq, 40 g / eq to 500 g / eq or 50 g / eq to 300 g / eq. [8] The epoxy resin composition according to any one of [1] to [7], wherein the content of epoxy resin (A) is 5% or more by mass, 8% or more by mass, 10% or more by mass, or 12% or more by mass, and / or 60% or less by mass, 50% or less by mass, 45% or less by mass, or 40% or less by mass. [9] The epoxy resin composition according to any one of [1] to [8], wherein the curing agent (B) is at least one selected from the group consisting of amine curing agents, acid anhydride curing agents and phenol curing agents, or is an amine curing agent.
[10] The epoxy resin composition according to any one of [1] to [9], wherein the amine curing agent is an aromatic amine, or is at least one selected from the group consisting of 4,4'-methylenebis(2-ethylaniline), ethyltoluenediamine, diethyltoluenediamine (3,5-diethyltoluene-2,4-diamine and 3,5-diethyltoluene-2,6-diamine, etc.), 1-methyl-3,5-diethyl-2,4-diaminobenzene, 1-methyl-3,5-diethyl-2,6-diaminobenzene, 1,3,5-triethyl-2,6-diaminobenzene, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,5,3',5'-tetramethyl-4,4'-diaminodiphenylmethane and dimethylthiotoluenediamine.
[11] The epoxy resin composition according to any one of [1] to
[10] , wherein the equivalent amount (molecular weight of each functional group) of the curing agent (B) is 10 g / eq to 300 g / eq, 20 g / eq to 160 g / eq or 30 g / eq to 100 g / eq.
[12] The epoxy resin composition according to any one of [1] to
[11] , wherein the content of curing agent (B) is such that the stoichiometric equivalent ratio (curing agent equivalent / epoxy group equivalent) with epoxy resin (A) is 0.5 to 1.5 or 0.8 to 1.2.
[13] The epoxy resin composition according to any one of [1] to
[12] , wherein the content of curing agent (B) is 2% or more by mass, 4% or more by mass, or 5% or more by mass, and / or 30% or less by mass, 20% or less by mass, 15% or less by mass, or 12% or less by mass.
[14] The epoxy resin composition according to any one of [1] to
[13] , wherein, as an inorganic filler (C), it comprises silica with an average particle size of less than 100 nm.
[15] The epoxy resin composition according to any one of [1] to
[14] , wherein the content of inorganic filler (C) relative to the epoxy resin composition (100% by mass) is 20% or more by mass, 30% or more by mass, 40% or more by mass, or 50% or more by mass, and / or 90% or less by mass, 80% or less by mass, or 70% or less by mass.
[16] According to the epoxy resin composition of
[14] , the content of silica with an average particle size of less than 100 nm relative to the inorganic filler material (C) (100% by mass) is 0.1% to 30% by mass, 0.1% to 20% by mass, 0.1% to 10% by mass, or 0.3% to 5% by mass.
[17] The epoxy resin composition according to any one of [1] to
[16] , wherein the shell layer in the core-shell rubber particle (D1) further contains at least one selected from the group consisting of methyl methacrylate and glycidyl methacrylate as a structural unit.
[18] The epoxy resin composition according to any one of [1] to
[17] , wherein the average particle size of the core-shell rubber particles (D1) is 0.03 μm to 1.0 μm, 0.04 μm to 0.8 μm, or 0.05 μm to 0.7 μm.
[19] The epoxy resin composition according to any one of [1] to
[18] , wherein the content of core-shell rubber particles (D) is 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, or 10% by mass or less, and / or 0.1% by mass or more, 0.5% by mass or more, 1.0% by mass or more, or 1.5% by mass or more.
[20] The epoxy resin composition according to any one of [1] to
[19] , wherein the content of core-shell rubber particles (D1) is 30% or less by mass, 25% or less by mass, 20% or less by mass, 15% or less by mass, or 10% or less by mass, and / or 0.1% or more by mass, 0.5% or more by mass, 1.0% or more by mass, or 1.5% or more by mass.
[21] The epoxy resin composition according to any one of [1] to
[20] , wherein the content of the core-shell rubber particles (D) relative to the total amount (100% by mass) of epoxy resin (A) and curing agent (B) is 1% to 60% by mass, 1% to 45% by mass, or 1% to 30% by mass.
[22] The epoxy resin composition according to any one of [1] to
[21] , wherein the content of core-shell rubber particles (D1) relative to the total amount (100% by mass) of epoxy resin (A) and curing agent (B) is 1% to 60% by mass, 1% to 45% by mass, or 1% to 30% by mass.
[23] The epoxy resin composition according to any one of [1] to
[22] , wherein the shell of the core-shell rubber particles (D1) is substantially free of styrene, acrylonitrile and methacrylonitrile as structural units.
[24] The epoxy resin composition according to any one of [1] to
[23] , wherein the epoxy resin composition is used for semiconductor sealing.
[25] A cured product, wherein the cured product is a cured product of any one of the epoxy resin compositions described in [1] to
[24] .
[26] A semiconductor device, wherein the semiconductor device comprises: substrate; Semiconductor elements disposed on the substrate; and The cured material described in
[25] that seals the semiconductor element.
[27] A method for manufacturing a semiconductor device, wherein the method for manufacturing the semiconductor device includes: The process of filling the gap between a substrate and a semiconductor element disposed on the substrate using any one of [1] to
[24] epoxy resin compositions; and The process of heating the epoxy resin composition to cure it. Industrial applicability
[0089] The epoxy resin composition of the present invention has low viscosity, thus exhibiting good workability. Furthermore, it has excellent injectability, enabling efficient filling of gaps in the epoxy resin composition even when manufacturing semiconductor devices using substrates such as large-scale interposers. Moreover, due to the aforementioned characteristics, it can contain a larger number of core-shell rubber particles compared to conventional epoxy resin compositions. Therefore, adjustments can be made to ensure that the cured epoxy resin composition exhibits a low elastic modulus. Consequently, semiconductor devices equipped with the cured epoxy resin composition can seal semiconductor elements with high precision using the cured composition, and exhibit high reliability due to the reduced stress applied to the cured epoxy resin composition. Explanation of reference numerals in the attached figures
[0090] 1 Test piece 2. Glass slides 2' glass slide 3 belts 4 gaps 5. Evaluate the samples.
Claims
1. An epoxy resin composition, wherein, The epoxy resin composition is an epoxy resin composition comprising epoxy resin (A), curing agent (B), inorganic filler (C), and core-shell rubber particles (D). As a core-shell rubber particle (D), it includes a core-shell rubber particle (D1) whose shell contains (meth)acrylic acid and (meth)acrylate as structural units.
2. The epoxy resin composition according to claim 1, wherein, The shell layer in the core-shell rubber particle (D1) further contains at least one selected from the group consisting of methyl methacrylate and glycidyl methacrylate as a structural unit.
3. The epoxy resin composition according to claim 1 or 2, wherein, The content of core-shell rubber particles (D1) relative to the total amount of epoxy resin (A) and curing agent (B) is 1% to 30% by mass.
4. The epoxy resin composition according to claim 1 or 2, wherein, The average particle size of the core-shell rubber particles (D1) is 0.03 μm to 1.0 μm.
5. The epoxy resin composition according to claim 1 or 2, wherein, The content of inorganic filler (C) relative to 100% by mass of epoxy resin composition is 50% by mass or more.
6. The epoxy resin composition according to claim 1 or 2, wherein, As an inorganic filler material (C), it contains silicon dioxide with an average particle size of less than 100 nm.
7. The epoxy resin composition according to claim 1 or 2, wherein, The epoxy resin (A) comprises at least one selected from the group consisting of bisphenol type epoxy resin, aminophenol type epoxy resin and naphthalene type epoxy resin.
8. The epoxy resin composition according to claim 1 or 2, wherein, Curing agent (B) is an amine-based curing agent.
9. The epoxy resin composition according to claim 1 or 2, wherein, The shell of the core-shell rubber particle (D1) does not substantially contain styrene, acrylonitrile, and methacrylonitrile as structural units.
10. The epoxy resin composition according to claim 1 or 2, wherein, The epoxy resin composition is used for semiconductor sealing.
11. A solidified material, wherein, The cured product is a cured product of the epoxy resin composition according to claim 1 or 2.
12. A semiconductor device, wherein, The semiconductor device includes: substrate; Semiconductor elements disposed on the substrate; and The cured product of claim 11 that seals the semiconductor element.
13. A method for manufacturing a semiconductor device, wherein, The method for manufacturing the semiconductor device includes: The process of filling the gap between a substrate and a semiconductor element disposed on the substrate using the epoxy resin composition according to claim 1 or 2; and The process of heating the epoxy resin composition to cure it.
Citation Information
Patent Citations
Liquid encapsulation material for copper bump and resin composition used for the same
JP2016108358A
Epoxy resin composition, underfill agent, cured product, and semiconductor device
JP2017171754A
Liquid resin composition for underfill, electronic part device and method for manufacturing electronic part device
JP2019081816A
